2012
DOI: 10.17221/300/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of grain of einkorn (Triticum mono-coccum L.), emmer (Triticum dicoccum Schuebl [Schrank]) and spring wheat (Triticum aestivum L.) varieties

Abstract: Wheat and cereals generally are largely consumed worldwide and contribute significantly to antioxidant intake with beneficial health effects. In the precise two-year field experiments, two varieties of wheat einkorn, two varieties of emmer wheat and three varieties of spring wheat in 2008 and moreover further two spring wheat varieties, three einkorn varieties and three emmer wheat varieties in 2009, were evaluated for antioxidant activity (AOA) using 2,2-diphenyl-1-picrylhydrazyl assay (DPPH). The higher grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
2
20
3
2
Order By: Relevance
“…[14]. While antioxidant values in our findings increase from diploid (einkorn) to tetraploid, the reverse is true for Lachman's results.…”
Section: Antioxidant Activity Of Different Wheat Speciescontrasting
confidence: 73%
See 3 more Smart Citations
“…[14]. While antioxidant values in our findings increase from diploid (einkorn) to tetraploid, the reverse is true for Lachman's results.…”
Section: Antioxidant Activity Of Different Wheat Speciescontrasting
confidence: 73%
“…This demonstrates a broad range of antioxidant content in wheat species. There were eight groups in which the means were not significantly different from one The findings of Lachman et al [14] showed that the antioxidant activity content of seven varieties ranged between 134.0 and 197.5 mg Trolox/kg DW. In this study, our results are approximately two times higher than these ones.…”
Section: Antioxidant Activity Of Different Wheat Speciesmentioning
confidence: 86%
See 2 more Smart Citations
“…Lachman et al (2011) found that higher selenium content in grain is related to emmer (58.9-68.4 μg/kg DM) and einkorn (50.0-54.8 μg/kg DM) accessions and varieties; in spring varieties selenium content was lower and ranged from 29.8 to 39.9 μg/kg DM. Selenium content is important because some soils are poor in selenium that is a trace mineral essential to human with beneficial impact on health and possess also antioxidant activity (Lachman et al 2012). Contrary, some heavy metals are very toxic (Cd, Pb) and there is an effort to decrease their content in wheat by treatment with brassinosteroids (Kroutil et al 2010).…”
mentioning
confidence: 99%